2002
DOI: 10.1289/ehp.02110399
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid exchanges and micronuclei in peripheral lymphocytes of shoe factory workers exposed to solvents.

Abstract: We examined sister chromatid exchanges (SCEs) and micronuclei (MN; cytokinesis-block method) in cultured peripheral lymphocytes from 52 female workers of two shoe factories and from 36 unexposed age- and sex-matched referents. The factory workers showed an elevated level of urinary hippuric acid, a biomarker of toluene exposure, and workplace air contained high concentrations of various organic solvents such as toluene, gasoline, acetone, and (in one of the plants only) ethylacetate and methylenediphenyl diiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 57 publications
0
20
0
1
Order By: Relevance
“…The individual data sets included in this pooled analysis revealed that the influence of GST genotype on micronucleus frequencies was statistically significant only in two (17,19) of the eight studies and only for GSTM1. Our finding confirms that pooled analyses, by increasing the statistical power, are adequate for assessing the involvement of genetic variants on genome stability and for resolving discrepancies among individual studies.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The individual data sets included in this pooled analysis revealed that the influence of GST genotype on micronucleus frequencies was statistically significant only in two (17,19) of the eight studies and only for GSTM1. Our finding confirms that pooled analyses, by increasing the statistical power, are adequate for assessing the involvement of genetic variants on genome stability and for resolving discrepancies among individual studies.…”
Section: Discussionmentioning
confidence: 91%
“…Data on GSTM1, GSTT1 genotypes, and micronucleus frequencies of the same subjects were collected from seven European laboratories. The database included data from articles already published (14)(15)(16)(17)(18)(19)(20), and from an unpublished study done at the University of Pisa, Italy (partially published in refs. 21,22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here too, however, evaluation is not possible as a result of inadequate documentation. In a publication about female workers in two shoe factories with exposure to a complex mixture of various solvents including MDI, an increase in micronuclei in the lymphocytes was described, but no increase in SCE (Pitarque et al 2002). In a second publication by the same research group, no DNA damage in monocytes was detected using the comet assay (Pitarque et al 1999).…”
Section: Genotoxicitymentioning
confidence: 99%
“…Nevertheless, interest in the oxidative damage caused by these solvents' toxic effects have only is relatively new, and thus the amount of evidence concerning their possible genotoxic and carcinogenic potential is scarce and still under discussion. Even though these substances are considered to be neither carcinogenic nor genotoxic to humans (IARC class 3 carcinogens, ie, not classifiable as to their carcinogenicity to humans), there is a growing amount of evidence suggesting increased (i) levels of markers of oxidative stress (10)(11)(12), (ii) rate of chromosomal aberrations or sister chromatid exchange (12)(13)(14), and (iii) incidence of various cancers among workers occupationally exposed to toluene or xylene [even at occupational exposures far below the respective occupational limits (15)(16)(17)(18)(19)(20)(21)]. Although precise mechanisms underlying the effects of toluene and xylene remain unknown, the role of oxidative stress, oxidative DNA damage and dysregulated cellular antioxidant levels have been implicated (22)(23)(24).…”
mentioning
confidence: 99%